THE EFFECTIVENESS OF USING THE NUMBER-CATCHING APE IN INTRODUCING NUMBERS TO CHILDREN AGED 4-5 YEARS AT PGRI NURUL IMAN TIWU ASEM KINDERGARTEN, CENTRAL LOMBOK - fathonatul husna (JOETAL: Journal of Education, Teaching and Learning, 2024)
This is caused by the lack of variety in the media used by teachers in schools. This research was carried out to increase children's interest in learning numbers through the use of an educational game tool in the form of a number-catching APE. The type of research used is mixed method by combining quantitative and qualitative methods. The research design used was explanatory sequential. The results of the research show (1) that the t-count value was 12.8, while the t-table value was 1.761. It can be concluded that t-count > t-table. So that Ha was accepted and Ho was rejected. This means that the use of APE rotating to capture numbers was effective in learning numbers for children aged 4-5 years at PGRI Nurul Iman Tiwu Asem Kindergarten with an effect size of 2.7 > 1.00 which included in the strong effect category.  (2) Supported by qualitative data from interviews with teachers and school principals that there was an increase in the recognition of numbers in children aged 4-5 years at PGRI Nurul Iman Kindergarten between before and after being given treatment in the form of APE rotating to catch numbers. Based on the quantitative and qualitative data obtained, the two data complement each other and do not conflict, so it can be concluded that the use of APE rotary capture of numbers is effective in introducing numbers to children aged 4-5 years at PGRI Nurul Iman Tiwu Asem Kindergarten. This means that qualitative data supports and strengthens quantitative data, because there is no difference between the two data.